Atendimento remoto por profissionais da saúde à população: revisão integrativa no contexto da pandemia - Moraes, Vanessa Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Introduction: The emergency scenario caused by the COVID-19 pandemic quickly established alternative approaches remotely, in order to carry out monitoring and assistance to the health of people. It is known that telemedicine has been used for over 20 years in health services and can be divided into two large sectors: telecare and tele education. Objectives: Identify the levels of evidence from the studies included in the integrative review; which professions and health professionals performed teleconsultation and by which means and virtual tools. Methods: This is an integrative literature review, methodology for obtaining, identifying, analyzing and synthesizing publications referring to a specific topic. The search was carried out in January 2021, delimiting the period of the last 5 years, in the following databases: Cinahl, Cochrane, Lilacs, Scopus, PubMed, Web of Science and Embase. The descriptors of the Dictionary of Health Science Specialties and MESH for terms in English were used. It was carried out in four phases: 1st phase: elaboration of the guiding questions of the review by the PICO strategy: "What are the levels of evidence of the studies included in the Integrative Review", "The professions and professionals who make use of teleconsultation" and "the means and virtual tools used for teleconsultation; 2nd phase: list the articles according to the listings from the literature searches, which were stored in the researchers' notebook; 3rd phase: carry out the analysis of titles and abstracts to the guiding questions; 4th phase: the articles included were analyzed according to the objectives, methodology, results and conclusions using specific instruments for the type of study: 10 Consolidated Criteria for Reporting Qualitative Research (COREQ), Strengthening the Reporting of Observational studies in Epidemiology (STROBE), Main Items for Reporting Systematic Reviews and Meta-Analyses (PRISMA). Results: the search returned 912 titles; first duplicates were excluded; analyzed the articles that answered the guiding questions; articles that did not have free online access were excluded; and the final sample consisted of 13 articles included in the review. The levels of evidence of the articles included according to the study design: six expert opinion articles, level of evidence VII; six of quantitative and descriptive design, with level of evidence VI; a systematic review of a qualitative and descriptive study, level of evidence V. The 13 articles were scored using the STROBE, COREQ and PRISMA instruments. The professionals and professions that use teleconsultation were: doctors, nurses, physiotherapists. The medical specialties identified were ophthalmology, orthopedics, urology, neurosurgery, plastic surgery and general practice. The means and tools used were: video calls; phone calls; email, Zoom platform, and Skype; iMessage and applications like R-MAPP. Discussion: The synthesis of knowledge of the 13 articles analyzed showed a common characteristic: adherence to distance care due to the emerging need for social distance and health recommendations to combat Covid-19. Conclusion: telemedicine represented in teleconsultation and teleservice were important means of health education and continuity of care; 13 articles with evidence levels V, VI and VII were included; the areas and professions that used teleservice and teleconsultation included the health team in general; some specialties of medicine used online and remote virtual assistance.

Introdução: O cenário de emergência causado pela pandemia da Covid-19 estabeleceu rapidamente abordagens alternativas de forma remota, a fim de realizar o monitoramento e assistência à saúde das pessoas. Sabe-se que a telemedicina vem sendo utilizada há mais de 20 anos nos serviços de saúde e pode ser dividida em dois grandes setores: teleassistência e teleducação. Objetivos: Identificar os níveis de evidência dos estudos incluídos na revisão integrativa; quais profissões e profissionais da área da saúde realizaram teleconsulta e por quais meios e ferramentas virtuais. Métodos: Trata-se de uma revisão integrativa da literatura, metodologia para obtenção, identificação, análise e síntese das publicações referentes a um tema específico. Foi realizada a busca em janeiro de 2021, delimitando o período dos últimos 5 anos, nas bases de dados: Cinahl, Cochrane, Lilacs, Scopus, PubMed, Web of Science e Embase. Foram utilizados os descritores do Dicionário das Especialidades das Ciências da Saúde e do MESH para termos em inglês. Foi realizada em quatro fases: 1ª fase: elaboração 8 das perguntas norteadoras da revisão pela estratégia PICO: “Quais os níveis de evidência dos estudos incluídos na Revisão Integrativa”, “As profissões e os profissionais que fazem o uso da teleconsulta" e “ os meios e ferramentas virtuais utilizados para a teleconsulta"; 2ª fase: relacionar os artigos conforme as listagens oriundas das buscas na literatura, que foram armazenadas no notebook dos pesquisadores; 3ª fase: realizar a análise de títulos e resumos às perguntas norteadoras; 4ª fase: os artigos incluídos foram analisados de acordo com os objetivos, metodologia, resultados e conclusões pelos instrumentos específicos ao tipo de estudo: Consolidated Criteria for Reporting Qualitative Research (COREQ), Strengthening the Reporting of Observational studies in Epidemiology (STROBE), Principais Itens para Relatar Revisões sistemáticas e Meta-análises (PRISMA). Resultados: a busca retornou 912 títulos; primeiramente foram excluídas as duplicidades; analisados os artigos que respondiam às perguntas norteadoras; excluíram-se os artigos na íntegra que não possuíam acesso on line grátis; e a amostra final foi composta de 13 artigos incluídos na revisão. Os níveis de evidência dos artigos incluídos de acordo com o delineamento do estudo: seis artigos de opinião de especialistas, nível de evidência VII; seis de desenho quantitativo e descritivo, de nível de evidência VI; uma revisão sistemática de estudo qualitativo e descritivo, nível de evidência V. Os 13 artigos foram pontuados pelos instrumentos STROBE, COREQ e PRISMA. Os profissionais e profissões que utilizam a teleconsulta foram: médicos, enfermeiros, fisioterapeutas. As especialidades médicas identificadas foram a oftalmologia, ortopedia, urologia, neurocirurgia, cirurgia plástica e clínica geral. Os meios e ferramentas utilizados foram: videochamadas; ligações telefônicas; e-mail, plataforma Zoom, e Skype; iMessage e aplicativos como o R-MAPP. Discussão: A síntese do conhecimento dos 13 artigos analisados apresentou uma característica em comum: a adesão ao atendimento à distância pela necessidade emergente do distanciamento social e recomendações sanitárias de combate a Covid-19. Conclusão: a telemedicina representada na teleconsulta e teleatendimento foram importantes meios de educação em saúde e continuidade de tratamento; 13 artigos com níveis de evidência V, VI e VII foram incluídos; as áreas e profissões que utilizaram o teleatendimento e teleconsulta incluíram a equipe de saúde de um modo geral; algumas especialidades da medicina utilizaram o atendimento virtual on line e à distância
Remote care by health professionals to the population: a review integrative in the context of the pandemic
Keywords: Pandemic; Health professionals; Telemedicine; Telemonitoring; Coronavírus; Pandemia; Telemedicina; Tele monitoramento; Profissionais da saúde; Coronavirus